2008
DOI: 10.1101/gad.1636008
|View full text |Cite
|
Sign up to set email alerts
|

PP2B and PP1α cooperatively disrupt 7SK snRNP to release P-TEFb for transcription in response to Ca2+ signaling

Abstract: The positive transcription elongation factor b (P-TEFb), consisting of Cdk9 and cyclin T, stimulates RNA polymerase II elongation and cotranscriptional pre-mRNA processing. To accommodate different growth conditions and transcriptional demands, a reservoir of P-TEFb is kept in an inactive state in the multisubunit 7SK snRNP. Under certain stress or disease conditions, P-TEFb is released to activate transcription, although the signaling pathway(s) that controls this is largely unknown. Here, through analyzing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
242
4
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(262 citation statements)
references
References 38 publications
15
242
4
1
Order By: Relevance
“…We also found that HMBA, SAHA, and JQ1 share a common mechanism of transcriptional activation (16,17,34). SAHA also affects histone acetylation, and JQ1 affects the "readout" of these marks by BRD4.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We also found that HMBA, SAHA, and JQ1 share a common mechanism of transcriptional activation (16,17,34). SAHA also affects histone acetylation, and JQ1 affects the "readout" of these marks by BRD4.…”
Section: Discussionmentioning
confidence: 53%
“…JQ1, HMBA, and SAHA Have Comparable Effects on HIV Transcription-This and previous studies suggested that HMBA, SAHA, and JQ1 share a common mechanism of transcriptional activation (16,17,34). To this end, we treated J⌬K cells with HMBA or SAHA alone or in combination with JQ1 for 24 h and measured the production of HIV by p24 capsid ELISA.…”
Section: Jq1mentioning
confidence: 92%
“…Such contact between Hexim1 and the Cdk9 activation segment accounts for its inhibition. Importantly, phosphorylation of S175 and T186 in the "T-loop" is required for P-TEFb assembly with Hexim1 and 7SK RNA (21,48,49). Like Hexim1, the HIV viral protein Tat interacts mainly with cyclin T1 and is known to compete with Hexim1 for association with P-TEFb (5,22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the outcome of the slow polymerase was an even greater decrease in miRNA synthesis. It is therefore anticipated that under certain physiological conditions in which PolII processivity is altered 40,41 or transcription re-initiation rate is regulated, 42 the effect on miRNA expression would be differential.…”
Section: Discussionmentioning
confidence: 99%